(untitled) (In situ, 2025)
Underwater archaeological research in the bay of Caska on the island of Pag continued from May 4 to 19, 2024. During the first week, work resumed in Zone D of Sector 1, where it had stopped last year. In the second week, taking into account new discoveries, research continued in a small cove southeast of Tunera, called Mala Pošta. At this location, a row of wooden poles was discovered that probably supported operational waterfront along a large retaining wall, built to prevent erosion. At the location of Mrke Stene, further in the direction of Pod bužu cove, the remains of another scuttled boat were discovered. Given that the discovery occurred on the last working day, further investigation of the wreck is planned for the next research campaign.